Impetigo presenting as an acute necrotizing swelling of the lower lip in an adult patient - Ghafoor, Mohammed; Halsnad, Moorthy; Fowell, Christopher; Millar, Brian G. (Oral surgery, oral medicine, oral pathology and oral radiology, 2012)
The authors present an unusual case of an acute swelling of the lower lip and septicemia in a 35-year-old, recent immigrant male arriving from India. The patient presented in our emergency department with a 48-hour history of a worsening, painful swelling of the lower lip. On presentation, he was pyrexial and the lip was found to be acutely inflamed with honey-colored crusting, pustular lesions, and induration . A diagnosis of impetigo leading to necrosis of the lip was established, a rare phenomenon potentially resulting in significant tissue destruction. Appropriate medical management achieved a good outcome and prevented disabling tissue loss of the orofacial region.